Counting Chinese People in a Catholic Country: Religious Difference, Racial Discrimination, and the 1930 Mexican Population Census. Issue 4 (October 2019) - Augustine-Adams, Kif
Abstract : On May 15, 1930, in the small border town of Naco, Sonora, census enumerator Miguel Robles started to count. When he finished walking his assigned portions of Calle Hidalgo, Avenida Independencia, and Calle Morelos, he had enumerated 143 individuals, each of whom answered the single question regarding religious identity the same way: Catholic. A block over, a carpenter named Ignacio Ledgard left his tools for the day to canvas his own neighborhood, counting 252 individuals, including his own family. They also all identified as Catholic, except for two Chinese men with no religion.